Perbedaan Kadar Hemoglobin Ibu Hamil antara Wilayah Endemis dan Non-Endemis Cacing Buski di Kabupaten Hulu Sungai Utara - Januarsih Januarsih; Rita Kirana; Agus Rachmadi (Politeknik Kementerian Kesehatan Banjarmasin, 2026)
Anemia during pregnancy remains a major public health issue in Indonesia. One of the contributing factors is intestinal parasitic infection, such as (buski fluke), particularly in areas with poor sanitation and raw aquatic plant consumption. To compare hemoglobin levels among pregnant women in endemic and non-endemic areas of Fasciolopsis buski. This was a comparative cross-sectional study involving 124 pregnant women, consisting of 62 from endemic and 62 from non-endemic regions. Data were obtained through interviews, observations, and hemoglobin measurements using Hemocue®. Data were analyzed using an independent t-test at a 0.05 significance level. The mean hemoglobin level among pregnant women in endemic areas was 10.7 ± 1.1 g/dL, while in non-endemic areas it was 11.6 ± 1.0 g/dL. The t-test revealed a significant difference between the two groups (p = 0.001). The prevalence of anemia was 61.3% in endemic and 29.0% in non-endemic areas. There is a significant difference in hemoglobin levels between pregnant women living in endemic and non-endemic areas of Fasciolopsis buski. Endemicity of parasitic infection may contribute to higher anemia risk among pregnant women in endemic regions.